Floating treatment wetlands integrated with microbial fuel cell for the treatment of urban wastewaters and bioenergy generation - Colares, Gustavo Stolzenberg; Dell'Osbel, Naira; Barbosa, Carolina V; Lutterbeck, Carlos; Oliveira, Gislayne A; Rodrigues, Lucia R; Bergmann, Carlos P; Lopez, Diosnel Rodriguez; Rodriguez, Adriane Lawisch; Vymazal, Jan; Machado, Enio L (The Science of the total environment, 2021)
The objective of the present study was to develop a combined system composed of anaerobic biofilter (AF) and floating treatment wetlands (FTW) coupled with microbial fuel cells (MFC) in the buoyant support for treating wastewater from a university campus and generate bioelectricity. The raw wastewater was pumped to a 1450 L tank, operated in batch flow and filled with plastic conduits. The second treatment stage was composed of a 1000 L FTW box with a 200 L plastic drum inside (acting as settler in the entrance) and vegetated with mixed ornamental plants species floating in a polyurethane support fed once a week with 700 L of wastewater. In the plant roots, graphite rods were placed to act as cathodes, while on the bottom of the box 40 graphite sticks inside a plastic hose with a stainless-steel cable acting as the anode chamber. Open circuit voltages were daily measured for 6 weeks, and later as closed circuit with the connection of 1000 Ω resistors. Plant harvestings were conducted, in which biomass production and plant uptake from each of the species were measured. On average, system was efficient in reducing BOD5 (55.1%), COD (71.4%), turbidity (90.9%) and total coliforms (99.9%), but presented low efficiencies regarding total N (8.4%) and total P (11.4%). Concerning bioenergy generation, voltage peaks and maximum power density were observed on the feeding day, reaching 225 mV and 0.93 mW/m2, respectively, and in general decaying over the 7 days. In addition, plant species with larger root development presented higher voltage values than plants with the smaller root systems, possible because of oxygen release. Therefore, the combined system presented potential of treating wastewater and generating energy by integrating FTW and MFC, but further studies should investigate the FTW-MFC combination in order to improve its treatment performance and maximize energy generation.
Keywords: Family Characteristics; Wetlands; Ornamental plants; zdroje bioelektrické energie; mokřady; Waste Water; Bioelectricity; elektrody; Constructed wetland; Renewable energy; Electricity; odpadní voda; Bioelectric Energy Sources; Wastewater; elektřina; Phytoremediation; Electrodes; charakteristiky rodiny